USULAN PERBAIKAN KUALITAS PRODUK SARUNG TANGAN DENGAN METODOLOGI SIX SIGMA DI PT KAHATEX - Calista Phang, Novia
PT Kahatex is a textile manufacturing company in Indonesia. One of the company’s products that have strict quality standards is knitted gloves. For this product, the company set a target to reduce the product defects at least 2% from the previous year’s defect rate. The defect rate achieved in 2018 from the knitting area alone was 6,39%, hence the target for this area in 2019 was set to 4,39%. However, the actual defect rate reached in 2019 was 10,77%, or in other words there was an increase of 4,38%. Therefore, the aim of this study is to reduce the defect rate and to achieve the target set by company. To achieve that, alternative improvement solutions are designed by using Six Sigma methodology with the approach of DMAIC (Define, Measure, Analyze, Improve, and Control). In the define phase, Six Sigma project was defined to be carried out in the knitting process in KK8J (Kaos Kaki 8 J) area. In the measure phase, process stability was achieved and process capability measurement resulted in the sigma level of 3,83. In the analyze phase, Pareto analysis was done to determine the main types of defects to be prioritized, Delphi process was done to identify the root causes, FMEA (Failure Mode and Effect Analysis) was used to sort the root causes by the RPN (Risk Priority Number), value, and lastly another Pareto analysis was done to determine the root causes to be prioritized. The chosen types of defects were sizing errors, needle marks, and knitting holes, meanwhile the chosen root causes were incorrect tension adjustment, incorrect feeder position, dust and fibers from yarn that fly around the production area, operator forgetting to reset the machine, and thinned brush that doesn’t get replaced at appropriate time. In the improve phase, alternative solutions were designed to solve the chosen root causes. The proposed solutions were 1) to design tension dials with number indicators on it, 2) to design a standard procedure to check the position of the feeders, 3) to design closed yarn containers to prevent dust and fibers from flying around, 4) to design a poka-yoke system to remind operators about machine reset, and lastly 5) to design a record keeping system of the brush exchange schedule. In the control phase, the improved process documentation plan was planned out and we measure the improved process. After that, the process management plan was planned out as well. The steps done in this phase were based on plans to maintain the improved process. Based on the control phase, it is estimated that if the solutions were implemented, the defect rate will decrease to 5,91% and the sigma level value will increase to 4,02.